Deconstructing the Patriarchal Myth - Perkel, Adrian K (PINS-Psychology in Society, 2026)
This paper attempts to deconstruct the idea that patriarchy is the cause of women’s oppression, arguing for a more nuanced exploration of the developmental processes that contribute to gender identity. In particular, social processes that serve to distort normal affectional development in boys is explored, relating these to the masculine qualities that are held up in society as the norm for both genders, despite their being anathema to what psychology regards as healthy. This bias tends to delegitimise feminine characteristics and place women in a mental double-bind. Instead, this paper argues for the validity of the feminine, and questions absolutist feminist discourses which fail to account for broader systemic factors in the construction of gender.